2023
DOI: 10.3390/children10081340
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Ponseti Technique in Different Types of Clubfoot—A Single Center Retrospective Analysis

Abstract: Background: Clubfoot is a congenital deformity that can affect one or both of a newborn’s lower extremities. The main objective of the study is to evaluate and compare the outcomes of the Ponseti method for the management of different types of clubfoot. Methods: A retrospective analysis of 151 children with 253 clubfeet (idiopathic untreated, idiopathic recurrent, and syndromic) with at least one year of follow-up was conducted in four months after ethical approval. Data were collected with a structured profor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
0
1
Order By: Relevance
“…This reflects that nurse not participate in increasing the awareness of mothers about the condition, and instead of having role, the doctor became the major source of information. This finding agrees with Butt [40] who conduct study about -Outcomes of the Ponseti Technique in Different Types of Clubfoot-A Single Center Retrospective Analysis‖ and found that less than half of the studied mothers had information about clubfoot from doctor.…”
Section: Discussionsupporting
confidence: 87%
“…This reflects that nurse not participate in increasing the awareness of mothers about the condition, and instead of having role, the doctor became the major source of information. This finding agrees with Butt [40] who conduct study about -Outcomes of the Ponseti Technique in Different Types of Clubfoot-A Single Center Retrospective Analysis‖ and found that less than half of the studied mothers had information about clubfoot from doctor.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, almost every third patient was treated by the Ponseti method only, while the rest were treated by the Ponseti method along with additional surgical procedures. That is not in accordance with other studies [3,[45][46][47], describing the Ponseti method as the gold standard, superior for the treatment of clubfoot. This discrepancy could be potentially explained by the fact that the patients who were treated at the UCH were resistant to previous treatment by the Ponseti method only.…”
Section: Discussioncontrasting
confidence: 78%